Pocket Tutor Gynaecology - Keane, J. Jodi (Pocket Tutor, 2022)
Pocket Tutor Gynaecology provides an approachable, concise but comprehensive guide to the subject that is practical, straightforward and designed to give treating common gynaecological presentations. It is intended for those who wish to include regular gynaecological care in their future practise but also for the general student and junior doctor who needs a refresh before a clinical encounter. Clinical essentials and first principles chapters systematically outline key principles and anatomy and physiology, and the gynaecological lifespan is outlined in detailed chapters covering puberty, menstrual disorders, reproduction, and the menopause transition. There are also dedicated chapters covering common consequences of genital diseases, as well as childbearing, prolapse and incontinence and of gynaecological cancers. Throughout the book author has included practical tips, useful diagrams and clinical images, examination techniques and tips as well as management options and their theoretical underpinnings to aid the junior clinician.